Barriers and Strategies for Type 1 Diabetes Management Among Emerging Adults: A Qualitative Study. (May 2022) - Sawyer, Bailee; Hilliard, Elizabeth; Hackney, Kyle J; Stastny, Sherri
Purpose: Individuals in the emerging adult age group (18-30 years) with type 1 diabetes (T1DM) have unique medical and social needs. The purpose of this study was to observe barriers and strategies for diabetes management among emerging adults with T1DM. Methods: A qualitative grounded theory model was utilized. An open-ended approach with a telephone interview was designed to allow a deeper understanding of the T1DM experience. The participants were from a larger survey-volunteer participant group and were asked to complete 1 interview in spring 2020 (n = 21, diagnosed age: mean 15.00 ± 8.00, females, n = 19). The data were analyzed for cohesive themes using grounded theory. Results: Participants indicated three main barrier themes (physiology, environment, and insurance) and 3 barrier subthemes (mental health, lack of social support, and weather). Three main strategy themes to diabetes management were recognized (medical technology, access to social support, and physical activity). There were 2 strategy subthemes (social media and social accountability). Conclusions: Regular use of social media can be a key tool for social accountability while lack of social support and physiological shifts can be barriers to management of T1DM. Physical activity should be considered as part of an individualized plan for management of diabetes.